INFLUENCE WORK ETHICS, DIGITAL LEADERSHIP AND CULTURE ORGANIZATION TO PERFORMANCE ASN DI LOCAL GOVERNMENT REGENCY MAGETAN - Sriminingsih, Nanik; Kistyanto, Anang; Tri Wijayati Wardoyo, Dewie (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This research aims to analyze the influence of work ethics, digital leadership, and organizational culture on the performance of the State Civil Apparatus (ASN) at the Regional Secretariat of Magetan Regency. In the era of digitalization, transformation in organizational leadership and management practices is very important to improve employee performance and the quality of public services. This research uses quantitative methods with primary data obtained through questionnaires and secondary data from various literature sources. The number of samples taken was 91 respondents, calculated using the Slovin formula, with an examination method using the multiple direct relapse method with the help of SPSS 22. Based on the research results, it shows that the organizational culture variable has the most dominant influence on ASN performance, with a lower significance value than other variables. The digital leadership variable also shows a significant influence on ASN performance, while work ethics does not have a significant influence. And work ethics, digital leadership, and organizational culture simultaneously influence ASN performance, this has been proven to be true. This research emphasizes the importance of implementing a strong organizational culture and effective digital leadership in an effort to improve ASN performance and provide better public services in Magetan Regency. From this research, the author provides suggestions for the Regional Secretariat of Magetan Regency to pay attention to other factors apart from work ethics, digital leadership and organizational culture so that ASN performance improves. As well as strengthening organizational culture, increasing digital leadership, developing work ethics and optimizing ASN performance.